Federated services: smart service paradigm based on distributed data co-governance - JIA Xiaofeng; QIN Rui; WANG Shouwen; QI Hongwei; WANG Fei-Yue; LI Juanjuan; ZHANG Min; LIANG Xiaolong (智能科学与技术学报)
The acceleration of digital transformation has made data a core element driving technological innovation and economic growth. However, the widespread phenomenon of data island severely hinders data circulation and collaboration across different fields and organizations, making it difficult for data supply to meet the diverse needs of users, thus creating a dilemma in matching data supply and demand. Serving as the core link in the federated ecology and an important window for external empowerment, federated services provide an innovative solution for data circulation and utilization under the principle of distributed data co-governance, thereby enabling the intelligent matching of supply and demand. Firstly, this paper delves into the pivotal role of federated services within the federated ecology, and examines the relationship between federated services and federated ecology's key components. Secondly, it presents a five-layer basic framework of federated services and discusses its core advantages. On this basis, the paper proposes the key supporting technologies for federated services, including blockchain and decentralized autonomous organizations and operations, large language models and scenario engineering, distributed computing and edge computing, as well as encryption technology and privacy computing. Finally, taking the supply-demand matching problem of data and scenarios as a case study, the paper illustrates how federated services achieve intelligent matching of demand and supply. The federated services proposed in this paper holds significant implications for constructing a smart service paradigm based on distributed data co-governance.